(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Meningitis is referred to as an inflammatory process of the leptomeninges and cerebrospinal fluid (CSF) within the sub-arachnoid space of the brain. We have investigated glucose status in CSF in different types of meningitis together with detailed medical history in children. In addition, we have also carried out the detailed cytological and microbiological examinations. A total of 40 subjects were investigated. We observed that the glucose level was significantly decreased (<20 mg/dl) in 65%, moderately decreased (20-40 mg/dl) in 20% and mildly decreased (40-50mg/dl) in 15% of the patients in our study. Patients with Pyogenic meningitis had tremendously reduced glucose level (9.0 mg/dl) in their CSF whereas in viral meningitis the CSF glucose level is highly variable (10 to 65 mg/dl). Furthermore, 5 (12.5%) patients showed high lymphocyte counts and 34 (85%) patients showed high neutrophil counts. Interestingly, in Pyogenic meningitis, the neutrophil count was very high compared to that in viral meningitis. The present study clearly demonstrates that biochemical parameters such as glucose level in CSF might be a potential tool for detecting meningitis and as well as differentiation of the different types of meningitis. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17080 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):41-49, 2011